Cognitive Adaptations Arising from Non-Native Experience of Sign Language in Hearing Adults - Keehner, Madeleine; Gathercole, S. (The Psychonomics Society, 2006)
Three experiments examined spatial transformation abilities in hearing people who acquired sign language in early adulthood. The non-native hearing signers were compared to hearing people with no knowledge of sign language, matched for age and gender. Using an adapted Corsi blocks paradigm, the experimental task simulated spatial relations in sign discourse but offered no opportunity for linguistic coding. Experiment 1 showed that the hearing signers performed significantly better than the nonsigners on a task that entailed 180 rotation, which is the canonical spatial relationship in sign discourse. Experiment 2 found that the signers did not show the typical costs associated with processing rotated stimuli, and Experiment 3 ruled out the possibility that their advantage relied on seen hand movements. We conclude that sign language experience, even when acquired in adulthood by hearing people, can give rise to adaptations in cognitive processes associated with the manipulation of visuospatial information.